2018
DOI: 10.4236/msce.2018.61006
|View full text |Cite
|
Sign up to set email alerts
|

Low Density Wood Impregnation with Water-Repellent Organosilicic Compounds

Abstract: Many protective treatments for low density wood are applied by impregnation to give water-repellency and to control pathologies that usually have this substrate. The properties of Araucaria angustifolia, chemically modified by impregnation with methyltriethoxysilane, n-octyltriethoxysilane and mixtures of both in several ratios, were investigated to achieve mainly high dimensional stability, low capillary water absorption as well as satisfactory water vapor permeability. The aforementioned impregnants produce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
(10 reference statements)
1
3
0
Order By: Relevance
“…For oven-dried white spruce wood, it was found that treatment with organosilanes with the wet step (OWSSiHT) gave better results (SD Gr and Rr: 45% and Gt and As a conclusion of this test, the best dimensional stability (radial and tangential) is 35% for oven-dried wood (OWSSiHT), 32% for air-dried wood (AWSSiT), and 27% for green wood (GWSSiT). These results are similar and even better than using the nano-SiO 2 particles, which obtained a maximum dimensional stability of 27% for pine and beech [35] or 31% with MTMOS for Araucaria angustifolia [36].…”
Section: Dimensional Stability and Water Vapor Sorption Of Organosilasupporting
confidence: 54%
“…For oven-dried white spruce wood, it was found that treatment with organosilanes with the wet step (OWSSiHT) gave better results (SD Gr and Rr: 45% and Gt and As a conclusion of this test, the best dimensional stability (radial and tangential) is 35% for oven-dried wood (OWSSiHT), 32% for air-dried wood (AWSSiT), and 27% for green wood (GWSSiT). These results are similar and even better than using the nano-SiO 2 particles, which obtained a maximum dimensional stability of 27% for pine and beech [35] or 31% with MTMOS for Araucaria angustifolia [36].…”
Section: Dimensional Stability and Water Vapor Sorption Of Organosilasupporting
confidence: 54%
“…They have so far been applied to increase wood durability against fungi and termites, limit leachability of other wood preservatives, improve wood weathering performance, reduce its flammability and hydrophilicity, or as coupling agents to improve bonding strength in various composites [12][13][14][15][16][17]. They have also proved to penetrate and bulk the cell wall, forming a three-dimensional network of polysiloxane and wood polymers which improves dimensional wood stability [8,13,18]. Therefore, they were also tried for archaeological waterlogged wood conservation, and some of them proved effective in stabilisation of wood dimensions upon drying, which is one of the most crucial issues related to conservation of this type of wood [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…After the summary, the flowchart is shown in Figure 3: Simple cells are very sensitive to the edge information of objects in the input visual information, while complex cells have a larger receptive field than simple cells and are relatively insensitive to the location of features [24]. Simple cells output their processed visual signals to complex cells [25]. It can be seen that the cat's visual information system processes the externally input visual signals in a hierarchical manner.…”
Section: Least Square Mathematical Modelmentioning
confidence: 99%